Studies on the quaternary structure of Escherichia coli pyruvate oxidase - Stevens, D.J.; Gennis, R.B. (The Journal of biological chemistry, 1980)
Pyruvate oxidase is a peripheral membrane enzyme isolated from Escherichia coli. The enzyme catalyzes the oxidative decarboxylation of pyruvate to yield acetate plus CO2. The specific activity of the purified oxidase is stimulated 25-fold by lipids, and this lipid requirement has been the subject of previous studies. Since the enzyme is a tetramer at high protein concentrations (1 mg/ml) and is known to self-aggregate under certain conditions, the question arose as to whether the lipid stimulation observed in the steady state assay might be due to a change in the quaternary structure of the protein, either a dissociation or further association. This report is directed at determining the state of association of pyruvate oxidase under assay conditions by using fluorescence polarization. A photoreactive, nonspecific probe, 1-azidonaphthalene 5-sulfonate, was used to label the protein surface with an extrinsic fluorophore. It is concluded that under steady state assay conditions the oxidase remains tetrameric.